AS RELAÇÕES ENTRE CONFLITO TRABALHO-FAMÍLIA, BEM-ESTAR SUBJETIVO E BEM-ESTAR NO TRABALHO - Accardo, édille Mirna (2013)
The work-family conflict is a frequent phenomenon in contemporary societies where men and women share family and professional responsibilities, its direction can be unidirectional or bidirectional, i.e., family to work, from work to family or simultaneously from sphere to another. It significantly affects family relationships and relationships in organizations, thus directly affects the well- being of individuals. This study is a quantitative and cross-sectional design. The criterion for the selection of participants was the convenience. The objective of this research was to analyze the relationship between work-family conflict (WFC), subjective well- being (SWB) and well-being at work (WBW).The study involved the participation of 174 workers in a diverse sample of professionals in the private, public and NGO, with 52.9 por cento female, with average age from to 38.29 old years (SD=11.22). To obtain the data it was chosen chose a questionnaire covering all three study variables containing two scales to measure the dimensions of SWB, one of WBW and a scale to measure the WFC/FWC. For data analysis we used the SPSS, version 20. We calculated frequencies, percentages, means, standard deviations, and correlation coefficients, as well as reliability coefficients of the measures used (Cronbachs alpha). The results showed a greater interference of work in the family than in family work. This interference was significant for well- being at work and for the subjective well-being by changing the job involvement and generating feelings of unhappiness, depression and anxiety about their personal achievements, and about the future. The higher the work-family conflict, the lower well- being at work and lower the subjective well-being of those participating.